Luminescent zinc oxide nanoparticles: from stabilization to slow digestion depending on the nature of polymer coating. Issue 1 (22nd November 2018) - Zheng, Zhiqin; Mounsamy, Margaux; Lauth-de Viguerie, Nancy; Coppel, Yannick; Harrisson, Simon; Destarac, Mathias; Mingotaud, Christophe; Kahn, Myrtil L.; Marty, Jean-Daniel
Abstract : PEG- b -PAA and PEG- b -PVPA copolymers stabilize luminescent ZnO NPs in THF and enable their transfer to water. Abstract : Poly(ethylene glycol)-poly(vinylphosphonic acid) and poly (ethylene glycol)-poly(acrylic acid) block copolymers (PEG- b -PVPA and PEG- b -PAA) were synthesized by RAFT/MADIX polymerization. The interaction of PAA or PVPA blocks with preformed ZnO NPs and the presence of a highly soluble PEG block enable a stable colloidal solution of ZnO NPs to be obtained in both organic solvent and water. While in THF a significant enhancement of luminescent properties is observed in both cases, a slow decrease of these properties is observed in water, which is due to the slow digestion of the ZnO NPs. Lastly, compared to the PAA block, the PVPA block favors both the interaction with ZnO NPs and their digestion.